IMPLEMENTATION OF EDUCATIONAL MANAGEMENT INFORMATION SYSTEMS IN IMPROVING SCHOOL SERVICES - Ade Akhmad Saputra; Siti Nurhaliza; Arwan, Arwan (Balai Diklat Keagamaan Jakarta, 2025)
Abstract This study aims to analyze the implementation of the Education Management Information System (EMIS) in improving school services at SD Negeri 12 Banyuasin. This study uses a qualitative approach with a descriptive method. Data collection techniques include in-depth interviews, non-participant observation, and document analysis. Informants in this study include the school principal, teachers, the school committee, and parents of students. Data analysis techniques are conducted through the stages of data reduction, data presentation, and systematic drawing of conclusions. The study’s results indicate that implementing a web-based Education Management Information System can enhance administrative efficiency, increase information transparency, and promote parent involvement in education. This system facilitates access to educational programs, extracurricular activities, and student development, thereby supporting more effective and data-driven school management. The findings also show a decrease in administrative errors, an improvement in decision-making quality, and strengthened communication between the school and the community. However, challenges such as limited human resources, inadequate technical training, and technological access gaps remain obstacles. To address these issues, it is recommended that human resource capacity be strengthened, infrastructure optimized urgently, and community outreach enhanced. Overall, the Education Management Information System is a significant innovation that enhances the quality of school services transparently and efficiently. Abstrak Penelitian ini bertujuan untuk menganalisis penerapan Sistem Informasi Manajemen Pendidikan (EMIS) dalam meningkatkan layanan sekolah di SD Negeri 12 Banyuasin. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Teknik pengumpulan data meliputi wawancara mendalam, observasi non-partisipan, dan studi dokumentasi. Informan dalam penelitian ini meliputi kepala sekolah, guru, komite sekolah, dan orang tua siswa. Teknik analisis data dilakukan melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan secara sistematis. Hasil penelitian menunjukkan bahwa penerapan SIM Pendidikan berbasis situs web mampu meningkatkan efisiensi administrasi, transparansi informasi, serta keterlibatan orang tua dalam pendidikan. Sistem ini mempermudah akses terhadap program pendidikan, kegiatan ekstrakurikuler, dan perkembangan siswa, sehingga mendukung manajemen sekolah yang lebih efektif dan berbasis data. Temuan juga menunjukkan adanya penurunan kesalahan administrasi, peningkatan kualitas pengambilan keputusan, serta penguatan komunikasi antara sekolah dan masyarakat. Meskipun demikian, kendala seperti keterbatasan sumber daya manusia, pelatihan teknis yang belum memadai, serta kesenjangan akses teknologi masih menjadi hambatan. Untuk mengatasi hal tersebut, disarankan adanya penguatan kapasitas SDM, optimalisasi infrastruktur, dan peningkatan sosialisasi kepada masyarakat. Secara keseluruhan, SIM Pendidikan merupakan inovasi penting dalam meningkatkan mutu layanan sekolah secara transparan dan efisien.